Multi level distributors perceptions on mobile commerce / ShahrulNizam Ahmad - Ahmad, ShahrulNizam (2006)
The purpose of this research was to determine the perceptions of Multi Level Distributors on Mobile Commerce. TAM (technology acceptance model) for wireless internet model was tested in verifying its applicability and relevancy of the research model constructs in determining the distributors' perceptions on mobile commerce. In addition, this research also aimed to identify the distributor's preferred sales and business applications that could be implemented in mobile commerce for the multi level marketing sector. This research employed a 'Questionnaires method' and targeted all level of distributors from one of the biggest Shaklee's group in Malaysia which called as Shaklee Dynamic Family Group. A final sample of 42 responses out of 70 distributed questionnaires was analyzed. TAM (technology acceptance model) for wireless internet model was found to be applicable and relevant to determine the distributors' perceptions on mobile commerce. The results indicated that the majority of the distributors were innovative and exposed to the internet technology. This group of distributors had also given positive perceptions on mobile commerce. In addition, the result also indicated the distributors' preferred sales and business applications that could be implemented for mobile commerce. Overall, the research results had given a positive signs for creating mobile commerce as a new business channel for multi level marketing in the future.